Significados permanentes e mutantes: sociabilidades e significações no cotidiano de um café - Letícia Dias Fantinel; Neusa Rolita Cavedon; Tânia Maria Diederichs Fischer (Ciências Sociais Unisinos)
This article aims to unravel the meanings attributed to the organizational space by clients of a café, relating this phenomenon to cultural circularity and its reinterpretation and understanding it in the light of the meanings that cafés received historically. To achieve this, an ethnographic study was developed, in which we adopted techniques of systematic and participant observation, plus in-depth interviews. For the analysis of field data we used content analysis. The categorization and analysis of the data allowed us to identify repertoires of meanings that emerged from the field, which highlight the complexity inherent in the management of organizations whose core business is sociability. We perceived the historical continuity of meanings related to conviviality and shared space, but also unveiled meanings that reinforce contemporary aspects of the organization, such as those that refer to individuality and urban violence. The discussion of such aspects implies new challenges to contemporary management, considered from the perspective of organizational sociability and the survival of cafés as organizations that can contribute to innovations in building shared urban spaces.